Labeling Extracellular Vesicles for Nanoscale Flow Cytometry - Aizea Morales-Kastresana (Nature Portfolio, 2017)
Abstract Extracellular vesicles (EVs), including exosomes and microvesicles, are 30–800 nm vesicles that are released by most cell types, as biological packages for intercellular communication. Their importance in cancer and inflammation makes EVs and their cargo promising biomarkers of disease and cell-free therapeutic agents. Emerging high-resolution cytometric methods have created a pressing need for efficient fluorescent labeling procedures to visualize and detect EVs. Suitable labels must be bright enough for one EV to be detected without the generation of label-associated artifacts. To identify a strategy that robustly labels individual EVs, we used nanoFACS, a high-resolution flow cytometric method that utilizes light scattering and fluorescence parameters along with sample enumeration, to evaluate various labels. Specifically, we compared lipid-, protein-, and RNA-based staining methods and developed a robust EV staining strategy, with the amine-reactive fluorescent label, 5-(and-6)-Carboxyfluorescein Diacetate Succinimidyl Ester, and size exclusion chromatography to remove unconjugated label. By combining nanoFACS measurements of light scattering and fluorescence, we evaluated the sensitivity and specificity of EV labeling assays in a manner that has not been described for other EV detection methods. Efficient characterization of EVs by nanoFACS paves the way towards further study of EVs and their roles in health and disease.